Lost-time illness, injury and disability and its relationship with obesity in the workplace: A comprehensive literature review - Behdin Nowrouzi; Basem Gohar; Behnam Nowrouzi-Kia; Victoria Mintsopoulos; Alicia McDougall; Gillian Jordan; Jennifer Casole; Michel Lariviere; Angelo Tremblay (International Journal of Occupational Medicine and Environmental Health, 2016)
The objective of this study was to conduct a literature review examining predictors of lost-time injury, illness and disability (IID) in the workplace, with a focus on obesity as a predictor, and to evaluate the relationship between obesity and losttime IID. The study objective was also to analyze workplace disability prevention and interventions aimed at encouraging a healthy lifestyle among employees and reducing obesity and IID, as well as to identify research gaps. The search was conducted in several major online databases. Articles included in the review were published in English in peer-reviewed journals between January 2003 and December 2014, and were found to be of good quality and of relevance to the topic. Each article was critically reviewed for inclusion in this study. Studies that focused on lost-time IID in the workplace were reviewed and summarized. Workers in overweight and obese categories are shown to be at a higher risk of workplace IID, are more likely to suffer from lost-time IID, and experience a slower recovery compared to workers with a healthy body mass index (BMI) score. Lost-time IID is costly to an employer and an employee; therefore, weight reduction may financially benefit both – workers and companies. It was found that some companies have focused on developing interventions that aid reduction of weight and the practice of active lifestyle among their employees. Int J Occup Med Environ Health 2016;29(5):749–766